(untitled) (Research, Society and Development, 2022)
The Human Teeth Bank (BDH) is present in many institutions of higher education with courses in Dentistry, and its purpose is to allocate extracted human teeth for scientific research or pre-clinical training of academics, following the highest ethical principles. This study reviewed the literature on the importance of tooth banks in higher education institutions, presenting the general parameters for their structuring and functioning. The process of implantation of the Teeth Bank requires in addition to physical space, an internal regulation, equipment for adequacy of teeth, terms and documents of consent and donation. The correct physical and chemical suitability (disinfection and storage) of the teeth is fundamental for their safe handling, but should not interfere with their structural properties. In this context, the implementation of Teeth Bank enables teaching and research practices in a legalized and safe way, reducing the illegal trade in teeth and ensuring a significant destination for them.